2014
DOI: 10.3354/dao02761
|View full text |Cite
|
Sign up to set email alerts
|

New disease records for hatchery-reared sturgeon. I. Expansion of frog virus 3 host range into Scaphirhynchus albus

Abstract: In 2009, juvenile pallid sturgeon Scaphirhynchus albus, reared at the Blind Pony State Fish Hatchery (Missouri, USA) to replenish dwindling wild stocks, experienced mass mortality. Histological examination revealed extensive necrosis of the haematopoietic tissues, and a virus was isolated from affected organs in cell culture and then observed by electron microscopy. Experimental infection studies revealed that the virus is highly pathogenic to juvenile pallid sturgeon, one of several species of sturgeon curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 44 publications
3
50
1
3
Order By: Relevance
“…Furthermore, FV3 outbreaks have impeded efforts to restore populations of the critically endangered pallid sturgeon ( Scaphirhynchus albus ) in the Missouri River Basin of the USA . High-mortality epizootics were reported among young-of-the-year pallid sturgeon in 2001, 2009, and 2013 at the Blind Pony Hatchery in Sweet Springs, Missouri, USA (Chinchar and Waltzek 2014 ;Waltzek et al 2014 ). Experimental transmission of the 2009 isolate recreated the same high-mortality disease in naïve juvenile pallid sturgeon following bath exposure .…”
Section: Frog Virusmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, FV3 outbreaks have impeded efforts to restore populations of the critically endangered pallid sturgeon ( Scaphirhynchus albus ) in the Missouri River Basin of the USA . High-mortality epizootics were reported among young-of-the-year pallid sturgeon in 2001, 2009, and 2013 at the Blind Pony Hatchery in Sweet Springs, Missouri, USA (Chinchar and Waltzek 2014 ;Waltzek et al 2014 ). Experimental transmission of the 2009 isolate recreated the same high-mortality disease in naïve juvenile pallid sturgeon following bath exposure .…”
Section: Frog Virusmentioning
confidence: 87%
“…Recently, SCRV and FV3 have been repeatedly detected among hatchery-reared freshwater fi shes in North America and Asia (Woodland et al 2002b ;Prasankok et al 2005 ;Deng et al 2011 ;George et al 2014 ;Chinchar and Waltzek 2014 ;Waltzek et al 2014 ). Two genetically distinct but related ranaviruses, Singapore grouper iridovirus (SGIV) and grouper iridovirus (GIV), have negatively impacted grouper mariculture in Asia since the 1990s (Chua et al 1994 ;Murali et al 2002 ;Qin et al 2003 ).…”
Section: Ranaviruses Infecting Fishmentioning
confidence: 99%
“…Johnson et al ( 2007 ) could only induce infections in a box turtle ( Terrepene ornata ornata ) and several redeared sliders with intramuscular injections of Burmese star tortoise ranavirus, but those that were orally exposed to the same dose remained uninfected. More recently, however, Brenes et al ( 2014a ) demonstrated water-borne transmission of an FV3-like ranavirus isolated from pallid sturgeon ( Scaphirhynchus albus ; Waltzek et al 2014 ) to red-eared sliders: 20 % of turtles that were bath exposed and 30 % of turtles co-housed with infected Cope's gray treefrog ( H. chrysoscelis ) became infected. It should also be noted that transmission by arthropod vectors has not been ruled out.…”
Section: Ranavirus Transmission Within a Speciesmentioning
confidence: 99%
“…2a ; Waltzek et al 2014 ), and fi sh may have red swollen gills . Internally, hemorrhages may occur in any organ including the fat bodies and swim bladder, and organs may be friable (Fig.…”
Section: Fishmentioning
confidence: 99%